"n Multidissiplinêre benadering tot Praktiese Ekklesiologie - Dreyer, Wim A. (HTS teologiese studies, 2011)
A multi-disciplinary approach to Practical Ecclesiology In this contribution the author proposes a multi-disciplinary approach to ecclesiology. Ecclesiology receives some attention in all theological disciplines; however, the various methods and approaches of the different disciplines leads to divergent results. This diversity in ecclesiology could be very positive if a multi-disciplinary approach could be developed. Contributions by theologians of the Netherdutch Reformed Church of Africa (NRCA) are used as an example of divergent approaches to ecclesiology. The conclusion is reached that Practical Ecclesiology could serve as a theological discipline where different ecclesiologies could be integrated to the benefit of theological training and the church in general.